2017
DOI: 10.1037/dev0000379
|View full text |Cite
|
Sign up to set email alerts
|

The development of marital tension: Implications for divorce among married couples.

Abstract: Marriages are often characterized by their positive and negative features in terms of whether they elicit feelings of satisfaction and happiness or conflict and negativity. Although research has examined the development of marital happiness, less is known about the development of negativity among married couples. We examined how marital tension (i.e., feelings of tension, resentment, irritation) develops within couples over time and whether marital tension has unique implications for divorce. Specifically, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Rather than the eight responsible actions, there may be at least eight negative and potentially destructive opposing behaviors that emerge when partners are not responsive. These include (a) criticism, hostility, and bitterness; (b) envy, irritation, and contempt; (c) enmity, coldness, and resentment; (d) busyness, personal pursuits, and digital distraction; (e) disregard and unsupportiveness; (f) revenge, defensiveness, and grudge holding; (g) sarcasm and mockery; and (h) unfaithfulness and selfishness (Birditt, Wan, Orbuch, & Antonucci, ; Gottman, ; Gottman & Silver, ; McDaniel & Coyne, ). However, even if these negative behaviors do not occur, if the positive responsible actions noted earlier occur without a responsive heart, they may be forced and unnatural—the outward behavior does not reflect responsiveness of one's heart to the Other.…”
Section: A Strong Relationality Model Of Meaningful and Flourishing Rmentioning
confidence: 99%
“…Rather than the eight responsible actions, there may be at least eight negative and potentially destructive opposing behaviors that emerge when partners are not responsive. These include (a) criticism, hostility, and bitterness; (b) envy, irritation, and contempt; (c) enmity, coldness, and resentment; (d) busyness, personal pursuits, and digital distraction; (e) disregard and unsupportiveness; (f) revenge, defensiveness, and grudge holding; (g) sarcasm and mockery; and (h) unfaithfulness and selfishness (Birditt, Wan, Orbuch, & Antonucci, ; Gottman, ; Gottman & Silver, ; McDaniel & Coyne, ). However, even if these negative behaviors do not occur, if the positive responsible actions noted earlier occur without a responsive heart, they may be forced and unnatural—the outward behavior does not reflect responsiveness of one's heart to the Other.…”
Section: A Strong Relationality Model Of Meaningful and Flourishing Rmentioning
confidence: 99%
“…A shortcoming of this research, however, is that it has not accounted for the multiple ways married couples can experience conflict over the course of their marriage. Some couples disagree or experience irritation on a regular basis, whereas others only disagree on occasion (Birditt, Wan, Orbuch, & Antonucci, 2017;Choi & Marks, 2008). Couples can also disagree across several important aspects of marital life, such as money, children, and relationships with in-laws (Oggins, 2003;Tamini, Raghibi, & Bakhshani, 2012).…”
mentioning
confidence: 99%
“…When the results are evaluated in terms of descriptive statistics, it is seen that as the marriage duration increases, the coparenting conflict increases and the joint management of the family relations decreases. Due to the increase in marriage conflicts as the marriage duration increases (Birditt, Wan, Orbuch, & Antonucci, 2017), this may affect the coparenting behaviors negatively. In addition, another important finding of the study was that parents with undergraduate and graduate education levels reported higher coparenting relationships than primary school graduate parents.…”
Section: Discussionmentioning
confidence: 99%